2004
DOI: 10.1530/eje.0.1510161
|View full text |Cite
|
Sign up to set email alerts
|

Is growth hormone deficiency contributing to heart failure in patients with beta-thalassemia major?

Abstract: A 21-year-old woman with b-thalassemia major (b-TM) and GH deficiency developed end-stage heart failure, New York Heart Association (NYHA) functional class IV, within 3 months after withdrawal of recombinant human growth hormone (GH). A myocardial biopsy excluded myocarditis and showed moderate iron deposit in the heart. Before her admission, intensified treatments with digoxin, angiotensin-converting enzyme inhibitor, diuretics and extra chelation therapy (desferrioxamine (DFO)) had not improved her progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Cardiac abnormalities are a consequence of the general comorbid conditions in thalassaemia but they may be closely related to concomitant endocrine deficiencies, hypercoagulability state, and inflammatory milieux [ 18 , 19 ]. Erfurth et al reported a normalization of cardiac function after GH treatment in a 21-year-old thalassemic female patient who developed end-stage heart failure, thus suggesting a contribution of GHD to heart deterioration [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac abnormalities are a consequence of the general comorbid conditions in thalassaemia but they may be closely related to concomitant endocrine deficiencies, hypercoagulability state, and inflammatory milieux [ 18 , 19 ]. Erfurth et al reported a normalization of cardiac function after GH treatment in a 21-year-old thalassemic female patient who developed end-stage heart failure, thus suggesting a contribution of GHD to heart deterioration [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to endocrine dysfunctions, dilated cardiopathy (DC) and chronic heart failure (CHF) are the pathologies that most exert a negative influence on quality of life, morbidity, and mortality in adult polytransfused patients [ 4 ]. Among several possible causes, impaired GH/IGF-I axis may contribute to cardiovascular outcomes in both polytransfused [ 2 , 10 ] and in nonpolytransfused patients [ 11 ], but in the literature, there is a lack of clinical data on this issue. The purpose of this observational study was to explore GH-IGF-1 axis function in a population of mainly adult polytransfused patients and correlate it with cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%
“…Other endocrinopathies common in thalassemia can also impact the heart. Hypothyroidism, 49 hypoparathyroidism, 50 low growth hormone, 51 and low testosterone 52 can reinforce ventricular dysfunction of any mechanisms. Vitamin (B1, D, folate), mineral (selenium, zinc), and metabolic cofactor (carnitine) deficiencies are common in thalassemia and can cause or worsen ventricular dysfunction and should be investigated in any patient with unexplained ventricular dysfunction 53–55 .…”
Section: Post Iron Cardiomyopathy Eramentioning
confidence: 99%
“…In fact, in the literature only case reports regarding cardiac failure secondary to decompensated hypothyroidism and hypoparathyroidism or heart failure associated with growth hormone deficiency are present. 5,6 Aim of our retrospective and cross sectional study was to establish the prevalence of cardiac complications in thalassemia major (TM) patients with endocrine diseases and to evaluate the influence of endocrine diseases on cardiac complications.…”
Section: Introductionmentioning
confidence: 99%